Citation Please: Executive Orders, DEI, and the Fight for Intellectual Freedom - Aisha M. Johnson (The Political Librarian, 2025)
This scholarship examines the ethical and professional implications of recent executive orders that directly affect the library and information science (LIS) field, particularly as they intersect with diversity, equity, and inclusion (DEI) initiatives, intellectual freedom, and cognitive liberty. While DEI training is intended to advance justice, representation, and accessibility, critics argue that mandates may infringe upon individual belief systems and privacy of thought. At the same time, federal restrictions on DEI and related cultural programs threaten the LIS profession’s long-standing commitment to inclusivity, neutrality, and equitable access to information. Through the lens of Antelman’s (2025) assertion on cognitive liberty and using legislative data on anti-DEI and anti-CRT measures, Johnson situates the LIS profession at a critical crossroads. Executive actions dismantling federal support for libraries, restricting cultural narratives, and curtailing public broadcasting create a chilling effect that undermines the library’s role as a neutral space for democratic engagement. The cumulative impact represents a dual erosion: ideological conformity imposed through policy, and structural disempowerment through defunding and censorship. The article argues that LIS professionals must confront these challenges by reaffirming the profession’s ethical commitments while advocating for approaches that safeguard both inclusivity and intellectual freedom. Rather than framing DEI and intellectual freedom as opposing principles, the article calls for a pluralistic stance that honors individual rights and collective responsibility. In doing so, libraries can continue to serve as resilient spaces of inquiry, access, and representation in an increasingly polarized sociopolitical landscape.
Keywords: Executive Orders; DEI; Intellectual Freedom; Libraries; Trump Administration